1987
DOI: 10.1111/j.1476-5381.1987.tb11396.x
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic and non‐purinergic innervation in the cerebral arteries of the dog

Abstract: 1Possible involvement of sympathetic purinergic transmission in the neurogenic response of dog cerebral and basilar arteries was examined with the use of o,13-methylene ATP and adrenoceptor, cholinoceptor blocking agents. 2 In the isolated basilar arteries, electrical transmural stimulation produced a transient contraction which was frequently followed by a relaxation. This transient contraction was abolished after desensitization of P2-purinoceptors with x,1-methylene ATP or by treatment with guanethidine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The neurogenic contractile response induced by electrical transmural nerve stimulation was reduced, but not abolished by prazosin, a specific ao-adrenoceptor antagonist (Cavero & Roach, 1980 (Kugelgen & Starke, 1985;Sneddon & Burnstock, 1985;Kennedy et al, 1986;Muramatsu, 1986;Muramatsu & Kigoshi, 1987). These vessels respond well to low frequencies of nerve stimulation and the relative contribution of the purinergic component is inversely related to the frequency of stimulation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The neurogenic contractile response induced by electrical transmural nerve stimulation was reduced, but not abolished by prazosin, a specific ao-adrenoceptor antagonist (Cavero & Roach, 1980 (Kugelgen & Starke, 1985;Sneddon & Burnstock, 1985;Kennedy et al, 1986;Muramatsu, 1986;Muramatsu & Kigoshi, 1987). These vessels respond well to low frequencies of nerve stimulation and the relative contribution of the purinergic component is inversely related to the frequency of stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…The occurrence of noradrenergic-purinergic responses where a,#-methylene ATP has been shown to block selectively the ATP response has been well documented in many smooth muscle preparations, including the guinea-pig vas deferens (Meldrum & Burnstock, 1983), the mesenteric artery (Kugelgen & Starke, 1985;Muramatsu, 1986), the rat tail artery (Sneddon & Burnstock, 1985), the cat nictitating membrane (Duval et al, 1985), the rabbit ear artery (Kennedy et al, 1986), the dog cerebral artery (Muramatsu & Kigoshi, 1987) and the rabbit saphenous artery . It would appear for the hepatic artery of the rabbit also, that the sympathetic contraction consists of a noradrenergic and a purinergic component and that the purinergic response is mediated by ATP acting through postjunctional P2x-purinoceptors.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was used to demonstrate sympathetic cotransmission of NA and ATP in the dog basilar artery (Muramatsu et al, 1979(Muramatsu et al, , 1981 and rabbit pulmonary artery Su, 1980, 1982). In a follow-up study in the dog basilar artery, desensitization of P2X receptors with a,b-meATP was used in experiments to further demonstrate sympathetic cotransmission of ATP and NA (Muramatsu and Kigoshi, 1987). Release of ATP from sympathetic nerves has been measured directly, using the luciferin luciferase assay in guinea pig vas deferens, and the ATP was shown to be coreleased with NA (Kirkpatrick and Burnstock, 1987); however, this assay has had limited success in blood vessels, probably because of the lower levels of ATP released.…”
Section: Dual Control Of Vascular Tone By Perivascular Nerves Andmentioning
confidence: 99%
“…Most peripheral arteries produce sympathetic adrenergic responses, while studies on isolated cerebral arteries have revealed a variety of neurogenic responses and atypical features which cannot be explained simply by adrenergic mechanisms (Lee et al, 1976;Duckles & Bevan, 1976). For example, in the dog basilar artery, transmural electrical stimulation produces both contraction and relaxation which are resistant to al-and a2-adrenoceptor blocking agents (Muramatsu et al, 1981;Muramatsu & Kigoshi, 1987). There are also marked differences in the sensitivity of cerebral and peripheral arteries to various vasoconstrictor agents (Nielsen & Owman, 1971;Muramatsu et at., 1978).…”
Section: Introductionmentioning
confidence: 99%